Investigation And Prevalence Of Hepatitis B Virus Genotypes In Southern And Northern Districts Of Punjab, Pakistan - Gilani, Khadija; Kareem, Uzair; Badar, Rehana; Rafique, Alina; Khurshid, Samina; Manawar, Sidra; Farooq, Matyyab; Ishaq, Muhammad (Migration Letters, 2024)
This study aimed to evaluate the prevalence of Hepatitis B Virus (HBV) infection, analyze HBV mutations, and compare nucleotide sequences in HBsAg-positive patients across different districts of southern and northern Punjab, Pakistan. A cohort of over 100 HBsAg-non clearance (positive) subjects were chosen for this investigation. The findings revealed that both genotypes D and A were prevalent across all subgroups of HBV patients, including those with various liver diseases. Specifically, genotype D was predominant, accounting for 52% of acute cases, 28% of chronic cases, 7% of carrier cases, and 3% of cirrhosis/HCC cases. The age distribution with the percentage of HBV infection among the selected patients was as follows: the highest percentage was seen in the 21-30 years age group (24.4%), followed by the 51-60 years age group (21.1%), the 31-40 years age group (16.6%), the 41-50 years age group (14.4%), >61 years age group (11.1%), the 11-20 years age group (8.88%), and the 1-10 years age group (3.33%). Quantitative Polymerase Chain Reaction (qPCR) results indicated that 83.3% of patient samples tested positive for HBV, while 16.7% tested negative compared to the control group. The viral load analysis revealed that the majority of positive samples had viral loads ranging from 50,000 to 100,000 IU/ml (40%), followed by 100,000 to 500,000 IU/ml (29.3%), 10,000 to 50,000 IU/ml (16%), >500,000 IU/ml (8%), and the lowest proportion (6.66%) fell within the range of 1-10,000 IU/ml. Overall, genotype D (subtype D) was predominantly observed among the isolated viral agents. All samples were found to align with the NC_003977.2 reference sequence for the Hepatitis B virus (taxon: 10407), with sequence lengths ranging from a minimum of 354 base pairs to a maximum of 418 base pairs.